“Não, não vou por aí”: sobre a reação terapêutica negativa na clínica dos pacientes difíceis - Mourão, Maíra Mamud Godoi (2019)
This study is born as an attempt to find solutions to the impasses with which we find ourselves in the clinic of so-called difficult patients. A clinic characterized by narcissistic closure, paralyzes and negative therapeutic reactions, which produce countertransference feelings of devitalisation and hopelessness. Above all, this research is done as a clinicaltheoretical exercise of elaboration mobilized by the desire to cure the countertransference, when taken by these feelings before refractory patients. In this sense, throughout the study, we tried to cross among the different theoretical formulations on the subject, to weave possible articulations between them, in an effort to look for alternatives, also in the way of using theories, closure and paralysis. For this, the methodological path followed was to walk through the perspectives of what we recognize as the two great matrices of psychoanalytic thought: the freud-kleinian and the ferencziana, until arriving at a transmatricial perspective, the result of the efforts of contemporary authors in the direction of the articulation of these two great matrices, aiming at the expansion of our theories and techniques. To a large extent, this articulation meets the demands made by the clinic of difficult patients, paradoxical cases that will require listening and techniques that do not exclude, but are capable of the interlocking of drive and object, fantasy and trauma, intrapsychic and intersubjective dimension. Throughout this way, we could see how the clinical barrier represented by the negative therapeutic reaction, paradoxically promoted important advances in psychoanalytic thinking. Mainly, we have seen how the negative therapeutic reaction itself and its countertransferential effects can be reinterpreted, not as mere obstacles to treatment and improvement, but as a primordial way of updating traumatic experiences in the analyzing situation, opening the way to its transference and, consequently, the possibility of patient recovery